Study on the Influence of Random Distribution of Inclusions on Gear Contact Fatigue Performance - Bing Lei; Huaiju Liu; Wenbo Zhang; Jiqiang Li (Jixie chuandong)
The existence of nonmetallic inclusions in gear materials can significantly reduce the contact fatigue strength of gears， and the research on the related mechanism can provide important guidance for the control of production quality and service evaluation. A finite element contact analysis model of gear pair with randomly distributed inclusions is established. Based on Brown-Miller multiaxial fatigue criterion， the influence of inclusion distribution characteristics on contact fatigue performance of gears is studied. The R-S-N curves of gear contact fatigue under three different reliability levels are predicted. The results show that， the presence of inclusions in the subsurface， especially the aggregation of inclusions， the considerable stress concentration will occur and the contact fatigue life will be significantly reduced. The minimum fatigue life depth is mainly in the range of 0.35bH to 0.75bH， and the statistical distribution is the most consistent with the logarithmic normal function， followed by the three parameter Weibull distribution function. The contact fatigue life conforms to the three parameter Weibull distribution better.